Natural Person and Legal Entity as a Guarantor in the Croatian Criminal Law - Vukušić, Ivan (LeXonomica, 2024)
The paper analyzes the specificity of unreal criminal offenses of omission, which is manifested in the fact that those criminal offenses are committed by the guarantor. Given the specificity and rarity of punishable conduct of omission, the paper analyzes the legal position of the guarantor (as a natural person or legal entity) whose duty is to protect certain, but not all, legal goods. In addition to the fact that responsibility for omission is exceptional, the statuses that individuals have in society are explained through the prism of the grounds of the guarantor duty in Croatian but also from the aspect of different legal systems. The concept of the legal bases of the guarantor’s responsibility, which represent the sources of unlawfulness and culpability in the guarantor’s duty, is elaborated in detail, with a special emphasis on the guarantor’s actions in mistake. Povzetek V prispevku je analizirana posebnost kaznivih dejanj neprave opustitve, ki se kaže v tem, da ta kazniva dejanja izvrši garant. Glede na specifičnost in redkost kaznivih dejanj opustitve članek analizira pravni položaj garanta (kot fizične ali pravne osebe), katerega dolžnost je varovati določene, vendar ne vseh pravnih dobrin. Poleg dejstva, da je odgovornost za opustitev izjemna, so položaji, ki jih imajo posamezniki v družbi, pojasnjeni skozi prizmo razlogov za dolžnost garanta na hrvaškem, pa tudi z vidika drugih pravnih sistemov. Koncept pravnih podlag garantove odgovornosti, ki predstavljajo podlage za protipravnost in krivdo pri garantovi dolžnosti, je podrobno obdelan, s posebnim poudarkom na delovanju garanta v zmoti.